On PRC's transition to the world market: a Comparative analysis between Zhuai and Shengzhen, the two SEZ (Special Economic Zones) neighbouring to Macau and Hong Kong - Murteira, Mário (2009)
Analysis of recent trends in the World Economic System. Economic Growth: from West to East. The cases of China and Macau.